MON-669 Diabetic Macular Edema Thickness in Asians and Caucasians: Is There a Difference? - Leung, Brian (J Endocr Soc, 2020)
Background: Diabetic macular edema (DME) is a manifestation of diabetic retinopathy (DR) which can result in vision loss. DME affects over 750,000 US adults over the age of 40, costing 33% more in Medicare dollars than those patients without DME. Ethnicity plays a role in the development of DR but there are no studies about DME and HbA1c in Asians versus Caucasians. As Asians are the fastest growing ethnic group in the US and are at an increased risk of developing Type 2 Diabetes Mellitus (T2DM), there is a need for more knowledge about DME compared to Caucasians. Purpose: Evaluation of diabetic macular edema thickness between Asian and Caucasian Diabetic patients. Methods: A retrospective chart review (2017-2019) of consecutive diabetic patients were performed at California Retina Clinic. Inclusion criteria: DME thickness was measured by Optical Coherence Tomography (OCT) (Heidelberg Spectralis, Heidelberg, Germany), OCT +/- 3 months of their HbA1c lab test, control (C) non-diabetic patients=HbA1c <6.0%; For T2DM patients diagnosed by primary care physician: HbA1c ≥6.0%. Exclusion criteria: Age under 18 or over 90 years. Data analysis: R Project version 3.6.1 (R Foundation for Statistical Computing, Vienna, Austria). Two-way ANOVA was used to determine the difference between the four groups. The post-hoc test, Tukey’s HSD was used for p-values (<0.05). Results: Of 500 consecutive patients: 80 patients met inclusion criteria: T2DM Asian (ADM), T2DM Caucasian (CDM), C Asian (CA), C Caucasian (CC). n=80 pts, avg age=59.187 years (sd=15.42, range 23-89 years), Female=44, Male=36; ADM: n=20, avg age=60.90 years (sd=11.22, range 37-79 years), Female=10,Male=10, HbA1c range = 6.7-11.9%, Avg HbA1c = 7.59%, Avg DME=276.28 um (sd=25.93 um, range = 238.5-342 um); CDM: n=20, avg age=68.05 years (sd=10.54, range 46-87 years), Female=9, Male=11, HbA1c range = 6.0-11.5%, Avg HbA1c = 7.52%, Avg DME=298.68 um (sd=33.84 um, range = 253.5-397.5 um); HbA1c in ADM v CDM: p=0.8(ns) CA: n=20, avg age=52.85 years (sd=16.81 years, range 34-84 years), Female=10, Male=10, HbA1c range = 4.8-5.5%; Avg DME=267.05 um (sd=21.09 um, range = 230-310 um). CC: n=20, avg age=62.95 years (sd=13.47 years, range 40-89 years), Female=14, Male=6, HbA1c range = 4.8-5.6%, Avg DME=285.68 um (sd=16.58 um, range = 248.5-312.0 um). ADM v CDM and DME [F(1, 76)=13.267, p = 0.00049]. Tukey’s HSD post hoc tests were carried out. CDM v ADM had a significantly higher avg DME: 22.4 um (p=0.031). Body Mass Index (BMI): ADM patients (avg= 25.6) compared to CDM patients (28.5):(p=0.05, t-test). Conclusion: In this small study, T2DM Asians had less macular edema thickness than T2DM Caucasians with similar HbA1c. T2DM Asian patients had lower Body Mass Index than T2DM Caucasians. Body Mass Index may be an additional factor to consider in the evaluation of diabetic macular edema in Asians and Caucasian Diabetic patients.